Necrotizing soft tissue infection of the fingertips secondary to paronychia in a leukemic child: a case report and warning - Li, Nannan; Zhang, Zhe; Lu, Yujie; Wu, Huanlin; Zhang, Yu; Cong, Fenghui (Frontiers in Pediatrics, 2026)
Acute lymphoblastic leukemia (ALL) is the most common childhood malignancy, for which chemotherapy remains the cornerstone of treatment. Skin toxicity is a frequent adverse reaction to chemotherapy; however, progression from paronychia to necrotizing soft tissue infection of the fingertips is uncommon. This report describes the case of a 7-year-old child with ALL who developed paronychia following combination chemotherapy with vincristine and daunorubicin. The infection progressed to involve multiple fingertips as necrotizing soft tissue infection, a course facilitated by the patient's underlying severe neutropenia. Raoultella ornithinolytica was identified on blood culture. A structured, multistep nursing protocol was implemented, including local disinfection, ethacridine lactate compresses, topical application of recombinant human epidermal growth factor solution and mupirocin ointment, and local oxygen insufflation. This regimen resulted in significant improvement of the lesions. Within 7 days, pain subsided, edema reduced by more than 50%, and joint mobility was largely restored, with complete clinical resolution achieved within 14 days. This case highlights the importance of early recognition of chemotherapy-induced skin toxicity and the value of standardized stepwise wound management in improving functional outcomes. It provides a practical reference for managing this rare yet severe cutaneous adverse reaction in children and underscores the critical role of specialized nursing in supportive oncology care.